Abortion: a legal issue and public health (Revista do Tribunal Regional Federal da 3ª Região, 2017)
Data from the Abortion National Research (PNA 2016) indicate that, in Brazil, 1 in 5,4 women with age up to 40 have already performed an abortion, which is commonly done in the ages that compose the core of the feminine reproductive system, that means, between 18 and 29 years old. The numbers of the post-abortion hospitalization calculated by the PNA are also high. The present study argues that the criminalization of abortion penalizes, mainly, the poor and uneducated women, which perform it in terrible sanitary conditions, putting their lives and health at risk, and that a democratic Law cannot criminalize the legitimate wish of not having undesired children, given that the simple prohibition cannot avoid this practice. Between 2004 and 2013, around 9 million women interrupted their pregnancies in Brazil, according to data from the Pan American Health Organization. Finally, it points the direct adoption as an alternative to abortion, having in mind the possibility of the genitors to transfer the guard of the child.
Keywords: Human rights; abortion decriminalization; direct adoption